The Impact of Digital Literacy on Academic Achievement and Students’ Learning Styles in Digital Learning Systems: A Systematic Literature Review - Armi Saputri Yanti Ikhsam; Rita Ewere Chukwuka; Muhira Dzar Faraby (Journal of Vocational, Informatics and Computer Education, 2026)
Purpose – The rapid transformation of higher education toward digital learning environments has increased the importance of digital literacy as a key competency for academic success. In digital learning systems, students are required to operate technology, critically evaluate information, regulate their learning processes, and adapt to diverse learning modalities. However, existing studies often examine digital literacy, academic achievement, and learning styles separately, resulting in fragmented understanding. This study aimed to systematically analyze the relationship between digital literacy, academic achievement, and students’ learning styles in higher education within digital learning systems. Methods – This study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. focusing on publications from 2020 to 2025 to capture recent post-pandemic developments, without restricting open-access status. After applying the predefined inclusion and exclusion criteria, 37 studies were included in the analysis. Data extraction was conducted using a standardized form, and the methodological quality of the included studies was assessed using the Mixed Methods Appraisal Tool (MMAT). Findings – The findings indicate that digital literacy significantly enhances students’ academic achievement, both directly and indirectly, through mediating factors such as technological self-efficacy, critical thinking, learning motivation, and self-regulated learning. In addition, digital literacy contributes to the transformation of students’ learning styles toward more autonomous, collaborative, and multimodal learning patterns. However, challenges such as unequal access to digital infrastructure, variations in students’ digital competencies, and limited pedagogical readiness among educators remain significant barriers to its implementation. Research implications – This study provides a comprehensive synthesis of the role of digital literacy in shaping academic outcomes and learning behaviors in higher education. These findings highlight the importance of integrating technological, pedagogical, and institutional strategies to optimize digital learning systems. Nevertheless, limitations related to database selection, time frame restrictions, and variability in study designs suggest the need for broader and more diverse future research.